Estratégia para a extração de astaxantina da farinha do resíduo de camarão (Litopenaeus vannamei) e avaliação da atividade antioxidante e antimicrobiana - Santos, Cleidijane Antero dos (2020)
Astaxanthin is the main carotenoid pigment found in shrimp residues, and has numerous beneficial properties for human health. The extraction of astaxanthin can be done using different organic solvents, however the use of these is being replaced by more sustainable options such as “Deep Eutectic Solvents” (DES), as they are considered an efficient alternative in the extraction of polar and nonpolar compounds. The objective of this work was to propose a strategy to increase the yield of the extraction of astaxanthin, from shrimp flour of the species Litopenaeus vannamei, using ethanol as extracting phase and DES (glycerol-choline chloride) and choline chloride as adjuvants with and without the use of ultrasound. The quantification of astaxanthin was done by spectrophotometer and high performance liquid chromatography (HPLC), the analysis of fatty acids by Gas Chromatography coupled to Mass Spectrometer (CG-MS) and the bioactive properties of the extracts were evaluated through antioxidant activity (by 2,2'-azino-bis 3-ethylbenzothiazoline-6- sulfonic acid - ABTS, and sequestration of the radical 1,1-diphenyl-2-picrilhydrazil - DPPH) and antimicrobial by modulation. The results show the ultrasound, the exposure time, as well as the use of DES are the factors that most interfere in the extraction of astaxanthin. Under conditions assisted by ultrasound, the addition of 5% (m / m) of shorter incubation times when compared to extractions involving only ethanol (maximum concentration of 30.99 µg / g of flour after 30 min). The analysis of the fatty acid profile showed a greater amount of polyunsaturated fatty acids. It was possible to obtain a value of 1.18 M inhibition of the ABTS radical, and 22.65% of the DPPH radical. The antibacterial activity showed a significant inhibitory effect at the minimum concentration of 1024µg / mL, whose values were statistically similar to those obtained from synthetic astaxanthin. The extraction process of astaxanthin using ethanol with the addition of 5% (m / m) of DES combined with ultrasound was efficient. These results add value to the product as it is extracted from a residue that allows the reduction of environmental impact in addition to the use of green solvents.